URGENSI BIMBINGAN PRA NIKAH DALAM MENGURANGI TINGKAT PERCERAIAN (STUDI DI KANTOR URUSAN AGAMA KECAMATAN KALIBARU KABUPATEN BANYUWANGI) - Sasmita Sari Sasmita Sari; Fathurrahman Alfa; Dzulfikar Rodafi (Jurnal Hikmatina, 2021)
The purpose of this study was to determine the Urgency of Pre-Marriage Guidance in KUA Kalibaru District. This is to find out how the implementation of pre-marital guidance at KUA Kalibaru District. Want to know the efforts that can be made by the District KUA in reducing the divorce rate in the Kalibaru District KUA. The results of this study indicate that the implementation of pre-marital guidance is in the form of collective marriage advice. When there is a catin registering their marriage, guidance will be carried out. The causes of divorce are due to economic factors, polygamy, lack of communication because some husband and wife partners do not follow pre-marital guidance. Efforts that can be made by the KUA in reducing the divorce rate are by providing pre-marital guidance to catin. There are inhibiting and supportive factors for KUA Kalibaru District in implementing pre-marriage guidance. In the end, the researcher recommends the Chairperson of the Office of Religious Affairs to be able to recruit mentors who are more competent and can master the material related to the dynamics of life about marriage and provide adequate facilities and infrastructure. Discipline the time to follow the guidance.